2017
DOI: 10.7554/elife.27187
|View full text |Cite
|
Sign up to set email alerts
|

The Sec61 translocon limits IRE1α signaling during the unfolded protein response

Abstract: IRE1α is an endoplasmic reticulum (ER) localized endonuclease activated by misfolded proteins in the ER. Previously, we demonstrated that IRE1α forms a complex with the Sec61 translocon, to which its substrate XBP1u mRNA is recruited for cleavage during ER stress (Plumb et al., 2015). Here, we probe IRE1α complexes in cells with blue native PAGE immunoblotting. We find that IRE1α forms a hetero-oligomeric complex with the Sec61 translocon that is activated upon ER stress with little change in the complex. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
73
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 53 publications
17
73
0
1
Order By: Relevance
“…Xtail uses Ribo-Seq data to measure changes in translation while accounting for changes in transcript abundance using RNA-Seq data to quantify the magnitude and statistical significance of differential translation efficiency (TE) genome-wide. Both TG and TM induced higher TE for ATF4, IFRD1, and SEC61G, which have been shown to be regulated during ER stress 5153 , as well as several other genes (Fig. 3c).…”
Section: Resultsmentioning
confidence: 84%
“…Xtail uses Ribo-Seq data to measure changes in translation while accounting for changes in transcript abundance using RNA-Seq data to quantify the magnitude and statistical significance of differential translation efficiency (TE) genome-wide. Both TG and TM induced higher TE for ATF4, IFRD1, and SEC61G, which have been shown to be regulated during ER stress 5153 , as well as several other genes (Fig. 3c).…”
Section: Resultsmentioning
confidence: 84%
“…Further in vitro and structural studies are needed to define the molecular interface mediating the IRE1-IRE1 interaction. Likewise, other ER lumenal and membrane proteins, such as BiP (Bertolotti et al, 2000), ERdj4 (Amin-Wetzel et al, 2017), Hsp47 (Sepulveda et al, 2018), and Sec61 (Sundaram et al, 2017) regulate IRE1 activity, and we have not studied how IRE1 may affect these interactions. And, we do not measure IRE1dependent RIDD activity (Hollien et al, 2009;Hollien and Weissman, 2006).…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, hyperactivated IRE1α can produce excess of XBP1 transcription factor, which can be beneficial for tumor cell growth in a hostile environment (Cubillos-Ruiz et al, 2017). Recent studies have identified many IRE1α interacting proteins that have been shown to regulate IRE1α activation and inactivation during ER stress (Eletto et al, 2014; Sundaram et al, 2017; Sepulveda et al, 2018). One of the key factors that regulate IRE1α activity is the luminal Hsp70 like chaperone BiP ATPase (Bertolotti et al, 2000; Okamura et al, 2000; Pincus et al, 2010; Amin-Wetzel et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unclear how the luminal protein BiP is efficiently recruited to the membrane-localized IRE1α in cells. Our previous studies have shown that IRE1α interaction with the Sec61 translocon is essential to regulate its oligomerization and RNase activity in cells (Sundaram et al, 2017). However, the molecular mechanism by which the Sec61 translocon limits IRE1α activity is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation